Do fall armyworm’s Metaflumizone resistante populations affect the activity of Trichogramma pretiosum? - M. G. Barbosa; S. A. Souza; T. P. P. André; A. D. S. Pontes; C. S. Teixeira; F. F. Pereira; P. L. Pastori (Brazilian Journal of Biology, 2021)
Abstract The possible interference of resistant pest’s populations to insecticides in natural enemies in the action thas not been clarified yet. Thus, this study aimed to evaluate Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) performance on Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) eggs with resistance frequency to the Metaflumizone over six generations of product exposure. Egg cards (2.0 x 7.0 cm) containing eggs from two populations of S. frugiperda, (resistant to Metaflumizone and the other susceptible), were exposed to T. pretiosum females for 24 hours in free-choice and no-choice testing in three generations (G1, G4, and G6). A completely randomized experimental design was used with 25 replications, each consisting of an egg card (experimental unit) containing 20 eggs. The parameters evaluated were: parasitism (%), emergence (%), sex ratio, number of emerged parasitoids per egg and males/females longevity. ANOVA and Tukey test (P≤ 0.05) were applied on the results. Results showed a reduction in parasitism [41.0% (G1) and 28.4% (G4)], egg emergence (17.5%) and parasitoids/egg [16.2 (G4) and 17.2 (G6)] in eggs originating from the population with resistance frequency. Females emerging from G6 populations eggs without exposure to Metaflumizone had greater longevity (3.5 days more) than the resistant population. The sex ratio and male longevity were not affected. The results indicate a reduction in T. pretiosum activity if S. frugiperda populations have some frequency of resistance to Metaflumizone.